(untitled) - Frisby, Craig L. (Hoboken, 2005)
The Comprehensive Handbook of Multicultural School Psychology highlights the latest research in this area and offers practical information on integrating issues of cultural diversity into research and practice.
Keywords: School psychology,Multicultural education; Handbooks, manuals, etc,Handbooks, manuals, etc